Srpski dobrovoljački korpus u Primorskoj Sloveniji 1944-1945. godine - Bojan Dimitrijević (Dileme, 2023)
The article provides an overview of the activities of the Serbian Volunteer Corps (SDK), which arrived at the Operational Zone of the Adriatic Littoral, specifically at what is now the Primorska region of Slovenia, in November 1944. The Corps reported to the Serbian Government and was used by the German military authorities to combat the resistance movements in occupied Serbia in 1941–1944. After the Soviet Army entered Yugoslavia and Serbia in the autumn of 1944, the Corps was transferred to the Operational Zone of the Adriatic Littoral. The article provides details on the SDK status, its size and role in this area and finally on its tragic fate, when most of its personnel that managed to withdraw to Austria were handed over to the Yugoslav Partisan forces, which executed them in remote areas of Slovenia. The article is based on the author’s archival research and on Serbian and Slovenian emigrant literature.